2013
DOI: 10.1007/s11096-013-9837-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacist service in the acute ward

Abstract: Background The majority of hospitalised patients have drug-related problems. Clinical pharmacist services including medication history, medication reconciliation and medication review may reduce the number of drug-related problems. Acute and emergency hospital services have changed considerably during the past decade in Denmark, and the new fast-paced workflows pose new challenges for the provision of clinical pharmacist service. Objective To describe and evaluate a method for a clinical pharmacist service tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 50 publications
(65 reference statements)
8
40
2
Order By: Relevance
“…This is less than the 44 min found in a comparable Danish study12 and longer than the 21.2 min found by Gleason et al 20. In general, it is difficult to compare results of time expenditures, since most studies do not state exactly what components were actually covered.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This is less than the 44 min found in a comparable Danish study12 and longer than the 21.2 min found by Gleason et al 20. In general, it is difficult to compare results of time expenditures, since most studies do not state exactly what components were actually covered.…”
Section: Discussionmentioning
confidence: 69%
“…An average reduction of 30 min between study groups was considered a clinically relevant difference in LOS. This was based on data from a study with a similar CP intervention taking 44 min 12. To take clustering into account, we used an intracluster correlation coefficient (ICC) of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…This enables the pharmacist to perform a more comprehensive medication review, as the pharmacist has more information available. In other models proposed for medication review in the acute hospital setting, the pharmacist meets the patient before the physician,12 which adds the element of obtaining the medication history and to conduct medication reconciliation before the actual review can be performed. A recent Danish study has shown that more medication-related problems are found, when medication reconciliation is also performed, but that the clinical importance is largest for problems found during medication review 24.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a recent systematic review could in 18 out of 31 studies not even determine if the pharmacists’ recommendations were passed on to the physician orally or in writing 2. A few, more recent, studies have published their methodologies in detail, one specific to the hospital setting,12 one specific to a primary care setting13 and one which can be used in both settings 14. The setting will likely influence the procedure for medication review, due to variations in access to the full medical record, laboratory results and contact with the physician and patient.…”
Section: Introductionmentioning
confidence: 99%
“…The acceptance rate of CP interventions varies considerably, ranging from 18% to 80% 11 13 17 18. One reason for this could be how interventions are communicated, which has been shown to influence the acceptance rate 11 13 19…”
Section: Introductionmentioning
confidence: 99%